2022
DOI: 10.5944/educxx1.30413
|View full text |Cite
|
Sign up to set email alerts
|

Variables personales y escolares asociadas a la inteligencia emocional adolescente

Abstract: El objetivo de este estudio fue conocer el nivel de inteligencia emocional en el periodo adolescente y analizar la existencia de diferencias significativas que puedan darse en la percepción, comprensión y regulación emocional en función de determinados factores personales y escolares. Participaron 4467 estudiantes de Educación Secundaria Obligatoria (ESO) de 12 a 16 años (M: 13.81; DT: 1.38) de la Comunidad Autónoma de Galicia, a los cuales se administró el instrumento Trait Meta MoodScale (TMMS-24). Los resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
20

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 0 publications
3
11
0
20
Order By: Relevance
“…The factor displaying the highest levels of emotional intelligence amongst the infant and primary education teachers in our study is emotional regulation, followed by emotional understanding and, finally, emotional perception. These data are similar to those published by Cazalla-Luna and Molero [ 31 ], Domínguez and Nieto [ 7 ] and Schoeps et al [ 43 ], Martínez-Saura et al [ 21 ] found that infant and primary education teachers exhibited high levels of emotional perception, then emotional regulation and, finally, emotional understanding. Suárez and Martín [ 2 ] reported that teachers in higher education obtained more significant levels in emotional understanding, then in emotional regulation and, finally, in emotional perception.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The factor displaying the highest levels of emotional intelligence amongst the infant and primary education teachers in our study is emotional regulation, followed by emotional understanding and, finally, emotional perception. These data are similar to those published by Cazalla-Luna and Molero [ 31 ], Domínguez and Nieto [ 7 ] and Schoeps et al [ 43 ], Martínez-Saura et al [ 21 ] found that infant and primary education teachers exhibited high levels of emotional perception, then emotional regulation and, finally, emotional understanding. Suárez and Martín [ 2 ] reported that teachers in higher education obtained more significant levels in emotional understanding, then in emotional regulation and, finally, in emotional perception.…”
Section: Discussionsupporting
confidence: 90%
“…Emotional intelligence is currently one of the best predictors of success in the academic and professional field [ 6 , 7 , 8 ]. Training in socioemotional skills holds tremendous potential in terms of boosting personal, career, academic, and social well-being amongst teachers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations